(untitled) (Significação: Journal of Audiovisual Culture, 2003)
From the distinction between rhetoric of argumentation and rhetoric o f figures, the author proposes the study o f the argumentative role of the figure rhetoric by analyzing its object and epistemological parameter. The object of the argumentative rhetoric is the social di scourse and i ts pragmatic efficiency. The rhetoric o f figures retakes the "elocutio" of the classic rhetoric and the expressive deviance of the rule. In both of cases, we have the attention focused on the enunciation processes, which evidence distinctive argumentative conflicts; however, undeniable possibilities of interaction with the reader are presented.